Relationship between Transformational Leadership of Head Nurse with Organizational Commitmentand Job Satisfaction of Professional Nurses as Perceived by Nursesat Tertiary Care Hospital Regional 2 - Kempech, Uncharee; Daengthern, Laddawan (NU Journal of Nursing and Health Sciences, 2019)
This descriptive research aimed to study relationship between transformational leadership of head nurses with organizational commitment and job satisfaction as perceived by professional nurses. Samples were 205 professional nurses working in regional health area 2. Instruments consisted of transformational leadership questionnaire, organizational commitment questionnaire and job satisfaction questionnaire which were tested for internal consistency reliability yielding Cronbach's alpha coefficient of 0.93, 0.95, and 0.96, respectively. Data were analyzed using percentage, mean, standard deviation, and Pearson's Product Moment Correlation Coefficient. Results revealed as follows; 1. Transformational leadership of head nurses as perceived by professional nurses was related with organizational commitment at a moderate level (r = .304). Transformational leadership of head nurses in terms of intellectual stimulation was mostly related with strong belief in acceptance of organizational values and goals at a moderate level (r = .357). Transformational leadership of head nurses in terms of individual consideration was related with willingness to work for organization at a low level (r = .189). 2. Transformational leadership of head nurses was related with job satisfaction at a low level (r = .259). Transformational leadership of head nurses in terms of inspiration was mostly related with satisfaction in terms of motivative factors at a moderate level (r = .322). Transformational leadership of head nurses in terms of individual consideration was significantly related with satisfaction in terms of hygiene factors at a low level (r = .176) (p = .001).